Normal physiologic coronary flow velocity gradient across the left anterior descending artery in healthy asymptomatic subjects - Fausto Rigo; Veronica Spadotto; Roberto Settimo Fattore; Pietro Renda; Christian Cugini; Maurizio Agnoletto (Exploration of Cardiology)
Aim: Coronary flow velocity (CFV) can be obtained with transthoracic echocardiography (TTE) in the left anterior descending coronary artery (LAD). The physiologic flow velocity gradient across the different segments of LAD has not been established. This study aims to assess the normal values of resting CFV in proximal, mid, and distal LAD. Methods: In a single center, prospective, observational study design, TTE was attempted on 110 consecutive, asymptomatic middle-aged subjects (age = 55 years, 46% males) with a low likelihood of coronary artery disease (< 5%). Resting CFV in the LAD was assessed with high-end machines, dedicated coronary pre-set, and high-frequency transducers by pulsed-wave Doppler under color-Doppler guidance in the proximal, mid, and distal segments. Results: The technical success rate for CFV imaging was lowest for the proximal (101/110, 92%), intermediate for mid (106/110, 96%), and highest for the distal segment (108/110, 98%). All 3 segments were interpretable in 101 subjects. CFV was highest in proximal segments (38.6 cm/s ± 3.9 cm/s), intermediate in mid segments (34.3 cm/s ± 6.04 cm/s, P < 0.01 vs. proximal), and lowest in distal segments (28.1 cm/s ± 1.7 cm/s, P < 0.01 vs. proximal and vs. mid). Conclusions: A resting evaluation of CFV-LAD can be obtained by TTE in the large majority of consecutive subjects referred to the echocardiography laboratory. Feasibility is highest for distal and lowest for proximal-LAD segments. There is a clear physiologic gradient of CFV with decreasing values, of about 10% for each step, going from proximal to mid and distal segments of LAD. When resting CFV is considered, the site of the sampling is important to obtain comparable and physiologically meaningful data.